TLR2 stimulation regulates the balance between regulatory T cell and Th17 function: a novel mechanism of reduced regulatory T cell function in multiple sclerosis - Nyirenda, Mukanthu H.; Morandi, Elena; Vinkemeier, Uwe; Constantin-Teodosiu, Dumitru; Drinkwater, Sophie; Mee, Maureen; King, Lloyd; Podda, Giulio; Zhang, Guang-Xian; Ghaemmaghami, Amir; Constantinescu, Cris S.; Bar-Or, Amit; et al. (American Association of Immunologists, 2015)
CD4+CD25hi FOXP3+ regulatory T cells (Tregs) maintain tolerance to self-Ags. Their defective function is involved in the pathogenesis of multiple sclerosis (MS), an inflammatory demyelinating disease of the CNS. However, the mechanisms of such defective function are poorly understood. Recently, we reported that stimulation of TLR2, which is preferentially expressed by human Tregs, reduces their suppressive function and skews them into a Th17-like phenotype. In this study, we tested the hypothesis that TLR2 activation is involved in reduced Treg function in MS. We found that Tregs from MS patients expressed higher levels of TLR2 compared with healthy controls, and stimulation with the synthetic lipopeptide Pam3Cys, an agonist of TLR1/2, reduced Treg function and induced Th17 skewing in MS patient samples more than in healthy controls. These data provide a novel mechanism underlying diminished Treg function in MS. Infections that activate TLR2 in vivo (specifically through TLR1/2 heterodimers) could shift the Treg/Th17 balance toward a proinflammatory state in MS, thereby promoting disease activity and progression.